The Emotional Components of Packaging and Consumers Preferences. The Importance of Promoting a Person’s Image and their Recognition - Wawrzynkiewicz, Natalia (Studia Oeconomica Posnaniensia, 2018)
The first contact of the consumer with a product occurs through the packaging. Usually this is the driver in the decision making process. This is what creates the consumers’ impression and emotions. The features of packaging are based on the interest in products. Contemporarily, it is important to remember that elements of packaging have impact on consumers decisions and preferences. The aim of this paper is to compare the constructive elements of packaging: visual and verbal ones. The subject of the survey was an examination of the visual attention paid to these elements in the cleaning products industry. The paper shows the differences between the perception of anonymous images of famous people appearing on product packaging. For the needs of the paper, the experiment was supported by a questionnaire and an eye tracking study. The analysis of the survey proved that an emotional element (the image of a person) attracted the majority of receivers attention. However, celebrity endorsement does not change purchase intention.